Autologous haematopoietic stem cell transplantation for Behçet's disease with pulmonary involvement: analysis after 5 years of follow up - Maurer, Britta; Hensel, Manfred; Max, Regina; Fiehn, Christoph; Ho, Anthony Dick; Lorenz, Hanns-Martin (Annals of the rheumatic diseases, 2006)
Background - Myeloablative chemotherapy and autologous haematopoietic stem cell transplantation (HSCT) may provide a therapeutic option in severe Behçet's disease (BD) with pulmonary involvement. - - Case reports - Two patients with BD with pulmonary involvement refractory to conventional immunosuppressive treatment underwent HSCT 1999. Stem cells were mobilised with cyclophosphamide (2 and 4 g/m2) and subsequently enriched ex vivo for CD34+ cells. The conditioning regimen used was melphalan (200 mg/m2). Outcome was measured by improvement of clinical features, function of affected organs, serological markers, need for immunosuppressive chemotherapy after transplant, and relapse. In both cases HSCT was successful, with good response and without serious complications. After 5 years of follow up one patient is in complete remission without immunosuppressive drugs and one has partial remission, needing low dose corticosteroids (8 mg/day). - - Conclusion - In these two patients myeloablative chemotherapy, followed by HSCT could be performed safely with marked improvement. In comparison with other observational studies the duration of more than 5 years of remission is remarkable, and its full duration is still unknown.